The Impact of Social Media Content Quality on Customer Engagement and Purchase Intentions in Micro and Small Businesses in Soppeng - Asnia Minarti; Andi Rahma Nur Alam; Andi Patappari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This study examines the effect of social media content quality on customer engagement and purchase intention among micro and small enterprises (MSEs) in Soppeng Regency. A quantitative survey was conducted with 120 social media users who had interacted with or purchased from local MSEs. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that content quality has a positive and significant effect on customer engagement; engagement positively affects purchase intention; and content quality also has a direct positive effect on purchase intention. In addition, customer engagement partially mediates the relationship between content quality and purchase intention. These findings highlight the need for MSEs to develop informative, relevant, and attractive content and to manage two-way interactions to increase conversion potential